Kualitas Organoleptik, Kandungan Lemak dan Nilai Oksidasi Lemak Se’i Daging Domba (Domba Rote) yang diberi Asap Cair Kayu Kusambi dengan Level yang Berbeda - Harlan Fadila Duru; Geertruida M. Sipahelut; Bastari Sabtu (JURNAL RISET RUMPUN ILMU HEWANI, 2026)
Se'i is a traditional smoked meat product from East Nusa Tenggara that is commonly processed using conventional smoking methods. The application of kusambi wood liquid smoke offers an alternative processing technology with more controlled quality and improved product safety. This study aimed to evaluate the effects of different levels of kusambi wood liquid smoke on the organoleptic quality, fat content, and lipid oxidation (thiobarbituric acid/TBA value) of Rote sheep se'i. A Completely Randomized Design consisting of four treatments, namely 0% (P0), 0.5% (P1), 1.0% (P2), and 1.5% (P3) liquid smoke, with four replications was employed. Organoleptic data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test, whereas fat content and TBA values were analyzed descriptively based on treatment responses. The results showed that different liquid smoke levels significantly affected (P<0.05) aroma, color, taste, overall preference, fat content, and lipid oxidation. The 1.5% liquid smoke treatment produced the highest organoleptic scores (aroma 4.16±0.69, color 3.62±1.34, taste 4.22±0.90, and overall preference 4.36±0.77), while yielding the lowest fat content (4.65±0.03%) and TBA value (2.59±0.02). These findings indicate that 1.5% kusambi wood liquid smoke effectively improves sensory quality while reducing lipid oxidation, making it a promising alternative to conventional smoking in the production of high-quality Rote sheep se'i.